UX Methodology as a Student-Centered Approach: Its Application in Designing Teaching Materials for Artistic Drawing: - Zúñiga Salas, Tatiana (2025)
After the pandemic, the use of technology has become part of everyday life in educational environments. With hybrid models, it is important for students to develop autonomous attitudes in their learning process. The goal of this article is to apply the UX methodology to the design of teaching materials for artistic drawing. In the UX methodology, the student is the center of their teaching-learning process and is involved in everything from the design to the evaluation of the products. The research adopts a qualitative approach to explore the implementation of the five UX phases: empathize, research, design, prototype, and test. The methodological design is classified as applied research of an existing methodology, using an exploratory cross-sectional approach to examine the performance of UX methodology in the context of artistic teaching materials. The researchers developed the study in three stages: the initial stage in 2020, the intermediate stage in 2021, and the advanced stage in 2024. For this purpose, we chose the Drawing 1 and Drawing 3 courses, which belong to the basic cycle of the curriculum of the School of Plastic Arts of the University of Costa Rica. The experience had the participation of 103 students. The results show the application of the empathy process, the research prior to the design, the development of two design systems, the evolution of the creation of three prototypes and the evaluation. The 2024 results confirm that UX methodology positively impacts the design of educational materials, fostering students’ sense of belonging and autonomy, which enhances learning and promotes personalized educational experiences.